Listeria ivanovii Infection in Mice: Restricted to the Liver and Lung with Limited Replication in the Spleen - Zhou, Mengying; Jiang, Mingjuan; Ren, Chenyan; Liu, Sijing; Pu, Qikang; Goldfine, Howard; Shen, Hao; Wang, Chuan (Frontiers in Microbiology, 2016)
Listeria monocytogenes (LM) vectors have shown much promise in delivery of viral and tumor antigens for the development of vaccines. Listeria ivanovii (LI) is a closely related bacterium with a similar intracellular life cycle that may offer advantages over LM because it is not a human pathogen, but can infect other animal species. Recent studies show that recombinant LI expressing M. tuberculosis antigens is effective in inducing protective immunity in mouse models, demonstrating the potential of LI as a live vaccine vector. However, a key barrier in the development of LI into a live vaccine vector is that its pathogenic and immunogenic characteristics have yet to be fully understood. Therefore, in this research, C57BL/6J mice were inoculated with LM or LI intravenously or intranasally, and bacterial loads, histopathologic changes, and cytokine production were determined at indicated days post inoculation. Results showed that after intravenous infection with LM or LI, bacteria were found proliferating in the liver, spleen and lung. However, LI could only reach a heavy burden in the liver and its ability to multiply and to resist host immunity seemed limited in the spleen and lung. After intranasal inoculation with LI, bacteria were mainly localized in the lung and failed to infect liver or spleen, while LM could. In organs with heavy LI burden, lesions were isolated, localized and densely packed, compared to lesions caused by LM, which were invasive. In the liver of intravenously inoculated mice and lung of intranasally inoculate mice, LI was able to elicit comparable cytokine production with LM and cause less severe histopathologic damages, and thus could be considered as a vector for treating or preventing hepatic or pulmonary diseases.